LEGAL ASPECTS OF INTERNATIONAL TERRITORIES IN THE SUBMARINE AREA - Nicolae PURDĂ (Challenges of the Knowledge Society)
United Nations Convention on the Law of the Sea held in Montego Bay in 1982, in Part XI, has established a radically distinct legal regime on soil and subsoil bottoms seas and oceans, beyond the limits of national jurisdiction of coastal States, different rules for other parts of the sea, including sea water above the free zone. The entry into force of the Convention of 1982 on November 16, 1994, was possible only after the adoption on 28 July 1994 in New York, of the Agreement on Implementation of Part XI of the Convention of 1982, which amends the legal regime of submarine territories beyond the limits of national jurisdiction established by the 1982 Convention.